Dinamika Perkembangan Keuangan Berkelanjutan di Indonesia: Tantangan dan Peluang Transisi Hijau - ELFRIDA YULIAR RASYIDIN (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2025)
Sustainable finance has become a strategic element in driving inclusive and environmentally friendly national development. This article examines the dynamics of sustainable finance development in Indonesia, highlighting the implementation challenges and strategic opportunities in accelerating the transition to a green economy. This study uses a descriptive qualitative approach with a literature study method on official documents, scientific journals, and policy reports from related institutions such as the OJK, Ministry of Finance, and international financial institutions. The results of the study show that although Indonesia has initiated various policies such as the Sustainable Finance Roadmap, Green Taxonomy, and the issuance of green sukuk, structural challenges still hamper optimal implementation, including low ESG literacy, regulatory disharmony, and limited bankable green projects. However, great opportunities remain open through community support, fintech development, green investment potential, and cross-sector collaboration. By strengthening regulations, incentives, education, and multi-party synergy, sustainable finance can become a major driver in the development of a resilient, equitable, and environmentally friendly national economy.